Assessment of lying down behaviour in temporarily crated lactating sows - G. Illmann; S. Goumon; H. Chaloupková (Animal, 2021)
Temporary crating may be a more acceptable housing system for lactating sows than permanent crating from an animal welfare point of view. It remains unclear whether opening the crate leads to changes in sow lying down behaviour and piglet activity that may pose an increased risk of injury to piglets. This study aimed to assess whether the lying down behaviour of lactating sows housed in temporary crating changed shortly after removal of confinement, whether it was influenced by piglets' behaviour and age and whether sows preferentially used some support during lying down after crate opening. Sows (n = 13) were crated from 5 days pre partum to 3 days post partum. Their behaviours were recorded on video over a 24-h period both preceding and following crate opening, as well as over a 24-h period on day 25. The following behaviours were analysed: position and activity of the piglets when the sow lie down, duration of the lying down events, use of pen walls or crate bars as support when lying down; and position of the sow in the pen when lying down. Piglet mortality was assessed every day. Data were analysed in SAS using GLM. The duration of lying down events did not differ between the 24-h periods before and after opening the crate but increased on day 25 (P < 0.01). Similarly, the percentage of piglets in the danger zone did not differ between the 24-h periods before and after opening the crate, but increased on day 25 (P < 0.0001). The percentage of piglets in the creep area increased temporarily the day after the crate opening (P < 0.0001). Sows frequently utilised support when lying down, but less over the 24-h period after the crate opening compared to the two other periods (P < 0.001). A higher percentage of piglets in the creep area resulted in longer lying down events where the sow's snout was in contact with piglets located in the creep area (P < 0.05). The present study shows that opening the crate does have an immediate impact on lying down behaviour and piglet behaviour, but it does not pose an increased risk to piglets. Our results also indicate that piglet behaviour changed with age and influenced sow lying down behaviour. Finally, our findings further suggest that some available lying down support may be a very important feature of the pen during the whole lactation period.